2017
DOI: 10.1159/000451085
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Epithelial Endocytotic Mechanisms of the Peanut Allergens Ara h 1 and Ara h 2

Abstract: Background: Peanuts are still one of the highest contributors to anaphylactic deaths after ingestion of a food allergen. At the molecular level, interactions between peanut allergens and the intestinal epithelium are largely unexplored. Previous findings by our research group demonstrated that the major peanut allergens, i.e., Ara h 1, Ara h 2, Ara h 3, and Ara h 6, were able to cross the Caco-2 human cell culture model of the intestinal epithelium. This research broadened our investigation to identify the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…In addition, TEER values were restored to their original levels, demonstrating the absence of any permanent damage on the monolayer caused by egg digests tested (Grootaert et al, 2017). In line with this, previous studies also reported that purified proteins from wheat (ω5-gliadin and LTP 1) (Bodinier et al, 2007), peach (Pru p 3 and LTP 1) (Tordesillas et al, 2013), and peanut (Ara h 1 and Ara h 2) (Price, Ackland, & Suphioglu, 2017) were able to cross Caco-2 monolayers without compromising cell monolayer integrity.…”
Section: In Vitro Models To Assess Tight Junction Disruption (Mie1)supporting
confidence: 72%
See 1 more Smart Citation
“…In addition, TEER values were restored to their original levels, demonstrating the absence of any permanent damage on the monolayer caused by egg digests tested (Grootaert et al, 2017). In line with this, previous studies also reported that purified proteins from wheat (ω5-gliadin and LTP 1) (Bodinier et al, 2007), peach (Pru p 3 and LTP 1) (Tordesillas et al, 2013), and peanut (Ara h 1 and Ara h 2) (Price, Ackland, & Suphioglu, 2017) were able to cross Caco-2 monolayers without compromising cell monolayer integrity.…”
Section: In Vitro Models To Assess Tight Junction Disruption (Mie1)supporting
confidence: 72%
“…Important to mention here is that many of these inhibitors (e.g. filipin, cytochalasinD and monodansylcadaverine) also affect viability as well as TEER values (Price et al, 2017). Little information with regard to the importance of various mechanisms of endocytosis is yet available for food allergens.…”
Section: In Vitro Models To Assess Receptor-mediated and Unspecific Ementioning
confidence: 99%
“…Previous investigations using a Caco-2 human cell culture model of the intestinal epithelium showed that the major allergens Ara h 1 and Ara h 2, as well as Ara h 3 and Ara h 6, can cross via these cells [32]. Price et al [33] recently specified the endocytic mechanisms by which Ara h 1 and Ara h 2 pass the Caco-2 cells. …”
Section: Discussionmentioning
confidence: 99%
“…11 Taking advantage of endocytotic inhibitors, Ara h 1 was proposed to utilize a combination of macropinocytosis and clathrin-mediated endocytosis for transportation, whereas Ara h 2 was suggested to utilize macropinocytosis and caveolae-mediated endocyotosis. 11 In a human organoid and a mouse-based approach, an IL-13-driven, CD38 cyclic adenosine diphosphate ribose-dependent process has been identified, which is responsible for the transfer of food allergens to lamina propria mucosal mast cells. 12 As suppression of these mechanisms resulted in the abrogation of food-induced allergic responses, these exciting data may add to knowledge of the benefit of blocking IL-13/IL-4 pathways.…”
Section: Food Allergy and Barrier Functionmentioning
confidence: 99%